2020
DOI: 10.1371/journal.pone.0231856
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding profile of women using a drospirenone-only pill 4 mg over nine cycles in comparison with desogestrel 0.075 mg

Abstract: Background Progestin-only pills are associated with irregular bleeding pattern including amenorrhea. Desogestrel 75mcg even being a pill that inhibits ovulation shows a poor cycle control that limits a more common use. A drospirenone (DRSP)-only pill was developed to improve the bleeding profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Bleeding pattern: control of bleeding profile with 4 mg DRSP in comparison to 75 µg desogestrel. A phase III clinical trial over 9 administration cycles compared bleeding profiles of women treated with 4 mg DRSP and women treated with 75 µg desogestrel [46,47]. The percentage of women with bleeding and spotting decreased in the 4 mg DRSP group from 69.2 % in administration cycle 2 to 56.3 % in administration cycle 9, and in the 75 µg desogestrel group from 74.05 % to 45.3 %.…”
Section: Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding pattern: control of bleeding profile with 4 mg DRSP in comparison to 75 µg desogestrel. A phase III clinical trial over 9 administration cycles compared bleeding profiles of women treated with 4 mg DRSP and women treated with 75 µg desogestrel [46,47]. The percentage of women with bleeding and spotting decreased in the 4 mg DRSP group from 69.2 % in administration cycle 2 to 56.3 % in administration cycle 9, and in the 75 µg desogestrel group from 74.05 % to 45.3 %.…”
Section: Tolerancementioning
confidence: 99%
“…In addition, during administration cycles 5 – 9, the proportion of women with prolonged bleeding (> 10 days) was significantly lower in the 4 mg DRSP group than in the 75 µg desogestrel group (p < 0.001). Premature study withdrawal due to abnormal uterine bleeding (AUB) occurred in 3.3% of DRSP and 6.6% of 75 µg desogestrel users (p < 0.001) 46 , 47 . In summary, the results of the clinical trials revealed that 4 mg DRSP controlled bleeding patterns better than did 75 µg desogestrel.…”
Section: Safetymentioning
confidence: 99%
“…Unscheduled bleeding days between the cycle 2–6 were lower in the DRSP group compared to the DSG; excluding the amenorrhoeic women (p = 0.0001, chi-square test). The mean [SD] number of bleeding days was 8.6 [8.52] days vs. 12.9 [16.47] days, p = 0.0233 [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one study a comparison between DRSP and desogestrel (DSG) was performed showing that in each cycle, up to cycle 7, the proportion of women with unscheduled bleeding including those which did not bleed was statistically significantly lower under the use of DRSP comparing it DSG (p = 0.0001, chi-square test). [16.47] days, p = 0.0233 [9].…”
Section: Bleeding Profilementioning
confidence: 93%
“…Excluding amenorrhoeic women following results were obtained: In the cycles 2-6, the proportion of women with unscheduled bleeding was statistically signi cantly lower in the DRSP group than in the DSG group (p = 0.0001, chi-square test). The mean [SD] number of bleeding days was 8.6 [8.52] days vs. 12.9 [16.47] days, p = 0.0233 [9].…”
Section: Bleeding Pro Lementioning
confidence: 99%